1996
DOI: 10.1097/00007890-199603270-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kidney Size on Cadaveric Renal Allograft Outcome1

Abstract: Chronic rejection is the commonest cause of long-term renal allograft loss. Though immunologic factors are thought dominant in its pathogenesis, nonimmunologic factors, in particular, hyperfiltration damage related to reduced renal mass, have also been proposed as factors in the causation of chronic allograft rejection. We assessed the influence of renal size on graft survival and function in all cyclosporine-treated cadaver donor adult renal allograft recipients engrafted at a single center between June 1989 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…In addition, these studies were restricted to living related donors, a situation in which functional graft loss is minimal as a result of the selection of healthy donors and in which several factors that are known to aggravate nephron loss in cadaver grafts are absent (see reference (18) for review). Two other studies were based on the analysis of kidney size (32) or volume (33) in cadaver donors and showed discordant effect on graft survival. Insufficient precision of nephron mass estimation, together with limited cohort sizes and statistical power, may explain some divergent results concerning the impact of kidney mass on transplant survival rate and late outcome (see reference (34) for review).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these studies were restricted to living related donors, a situation in which functional graft loss is minimal as a result of the selection of healthy donors and in which several factors that are known to aggravate nephron loss in cadaver grafts are absent (see reference (18) for review). Two other studies were based on the analysis of kidney size (32) or volume (33) in cadaver donors and showed discordant effect on graft survival. Insufficient precision of nephron mass estimation, together with limited cohort sizes and statistical power, may explain some divergent results concerning the impact of kidney mass on transplant survival rate and late outcome (see reference (34) for review).…”
Section: Discussionmentioning
confidence: 99%
“…There were 8 single-center studies, (10 -17) and it is likely that many of these single-center studies lacked adequate statistical power to test the hypothesis. Indeed, 4 studies included fewer than 200 patients (10,14,15,17). Many of the studies failed to use a multivariate analysis to eliminate possible confounding from the effects of other variables (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported reduced graft survival in situations in which the size of the donor kidney would be expected to be reduced in proportion to the size of the recipient (10,11). Other single-center studies found no effect of donor-recipient size mismatching on graft survival (12)(13)(14)(15)(16)(17). However, many of these studies may have lacked adequate statistical power to test the hypothesis rigorously.…”
mentioning
confidence: 99%
“…7,16 -19 The effect of kidney graft size and recipient weight (Rw) 20,21 has also been studied; however, the direct impact of matching the Kw itself (which correlates with both glomerular volume and nephron number) 15 to the Rw has been studied only in relatively small cohorts of Ͻ300 patients and only in living donors, 22,23 where the graft does not incur the same accumulating injuries as those from deceased donors.…”
mentioning
confidence: 99%